The Role of Ethnic Identity in Overcoming Discrimination Against Ethnic Minorities and Politics in Indonesia - Refly Setiawan; Dana Riksa Buana; Indah Pratiwi Tanjung (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Indonesia has a wide variety of ethnic, so it is very vulnerable to various conflicts such as discriminatory treatment of ethnic minorities. Despite laws prohibiting racial and ethnic discrimination, discriminatory acts still occur in some parts of Indonesia. Discrimination against ethnic minorities is a serious and complex problem and can take many forms, such as unfair treatment, negative stereotypes, exclusion, restrictions on access to resources and opportunities, and acts of violence and persecution that harm ethnic minorities. Some ethnic minorities that often experience discrimination in Indonesia include ethnic Chinese, Papuans, Dayaks, and several other ethnicities. One of the main causes of ethnic discrimination is due to prejudices and stereotypes that develop in society. These stereotypes often lead to the exclusion of ethnic minorities. Ethnic identity plays an important role in shaping perceptions, attitudes, and behaviors of individuals and groups, and can provide valuable insights for the management and handling of issues of ethnic discrimination. This can be the focus of research to identify how the role of ethnic identity can provide a deeper understanding of how ethnic identity can be used as a tool in addressing ethnic minority discrimination. The method in this study is qualitative descriptive with data collection techniques through literature studies such as journals, textbooks, handbooks, notes, and appendices related to the research topic, and the data analysis using content analysis. The results showed that to overcome the problem of ethnic discrimination, collective efforts from various parties are needed. In this regard, the role of media and education is very important to build awareness about diversity and reduce negative stereotypes. It is hoped that with awareness and cooperation from various parties, ethnic discrimination in Indonesia can be reduced and eliminated gradually.Keywords: Identity, Ethnicity, Discrimination, Stereotype, Minority